Maqashid Sharia Performance In Indonesian Islamic Banks: The Role Of Intellectual Capital And Sharia Supervisory Boards Cross-Membership And Gender Diversity - Vienka Ferenzha Salsabilla; Bima Cinintya Pratama; Hadi Pramono; Ira Hapsari (Universitas Muhammadiyah Sorong, 2023)
This study will examine the link between intellectual capital and maqashid sharia performance as well as the moderating effects of cross-membership and gender diversity of the sharia supervisory board to improve the influence of intellectual capital on maqashid sharia performance. The secondary source of data for this study was the yearly financial statements listed in the Indonesian Financial Services Authority between 2008 and 2020. The data analysis method used in this inquiry was a panel data regression model. The analytical techniques employed in this work include descriptive statistical tests, preliminary tests, and hypothesis testing. According to the results of the three preliminary tests that were used to develop the panel data regression model, this study uses the random effect model in models 1 and 2 to evaluate the relationship between intellectual capital elements and maqashid sharia performance. Cross-membership and the gender of SSB women are moderating factors. The results of this study show that intellectual capital influences Indonesian Islamic Banks' performance following maqashid sharia positively. This suggests that making better use of intellectual capital can improve a company's maqashid sharia performance. Cross-membership has a negative impact on maqashid sharia's performance, demonstrating that it will hinder the board's ability to focus and function effectively, which will lead to a decrease maqashid sharia performance. The results of this study demonstrate that the average female representation on the sharia supervisory board is only 4% of the total samples, meaning that it cannot affect maqashid sharia performance. Therefore, the female gender of the sharia supervisory board has no impact on maqashid sharia performance. In this study, there was no empirical support for the claim that gender diversity and cross-membership on sharia supervisory boards may increase intellectual capital for maqashid sharia performance.